Implementation of Prudential Banking Principles: State Responsibility in Combating Banking Crimes in Indonesia - Sulistyandari, Sulistyandari; Afwa, Ulil; Sutrisno, Putri Ayu; Nordin, Rohaida (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2024)
The primary function of banks is to gather public deposits and extend credit. While banks aim for profit, they also play a crucial role in enhancing societal welfare, which requires adherence to prudential principles. Unfortunately, banking crimes committed by managers often occur, adversely affecting both the institutions and the public. This study explores the application of prudential principles in banking as a state responsibility, the nature of violations associated with banking crimes, and the enforcement of Banking Law in Indonesia. The research analyzes court decisions related to banking crimes from 2015 to 2020, focusing on the relevant legal substances. Employing a judicial normative method that includes statutory, conceptual, and case analyses, the findings indicate that violations typically arise from managers with decision-making authority and access to internal data, leading to breaches of Banking Law and standard operating procedures (SOPs). Courts respond to these violations with criminal sanctions, while the Financial Services Authority (OJK) revokes licenses as necessary. Recommendations include appointing OJK supervisors with banking expertise and clarifying Article 49, paragraph (2), letter b of the Banking Law to prevent misinterpretation.